Rare presentation of metastatic adenocarcinoma of prostate as inguinal lymphadenopathy and its management - Nimbalkar, Ajay G.; Mehta, Sony B.; More, Vinal T. (International Surgery Journal, 2021)
Prostate cancer is among the top ten cancers in India. Approximately half of patients with prostate cancer have metastasis on presentation, bones and regional lymph nodes being most common. A case of metastasised cancer of prostate presenting only with an inguinal mass without any other symptom is rare. A 72-year-old presented with a right inguinal mass for six months without any other complaints. Biopsy of the inguinal mass was done, and histopathology showed metastatic adenocarcinoma. His serum PSA (prostate specific antigen) was 117.325 ng/ml. PET CT (positron emission tomography-computed tomography) showed PSMA (prostate specific membrane antigen) expressing lesion in left lobe of prostate involving left seminal with metastatic pelvic, right inguinal, retroperitoneal and mediastinal adenopathy with increased tracer uptake in sclerotic skeletal lesions in right iliac bone, acetabulum and right femoral shaft. TRUS (trans rectal ultra-sonography) guided biopsy of prostate (12 CORE) was performed and showed conventional prostatic adenocarcinoma with maximum Gleason score 4+4=8, grade group IV. The patient's clinical stage was T3b N1 Mb. Patient is currently on abiraterone with degarelix with normal repeat serum PSA (0.067 ng/ml) on follow up at 5 months. Metastatic prostatic carcinoma usually presents with iliac nodes or bony metastasis, but rarely they present with inguinal lymphadenopathy and should be dealt with high clinical suspicion as they are already in advanced stage of the disease process.